Avaliação de floresta nativa do bioma Mata Atlântica: uma aplicação da metodologia de custo de reposição - Carvalho, Frederico Costa (2013)
This study investigated the value of a native forest in the Atlantic Forest biome. For this, we used the methodology of replacement cost. In addition, we sought to clarify the main determinants of this value, as well as their impacts. Were formulated four research hypotheses, namely i) the level of degradation of the área does not influence the total cost of replacement of native forest , ii) rugged topography does not influence the total cost of replacement of native forest; iii) the distance from the area to be restored to the nearest urban center does not influence the total cost of replacement of native forest , and iv) the distance from the area to be restored to the nursery that supplies seedling does not influence the total cost of replacement of native forest. To reach the results were performed simple tests for mean differences for qualitative variables. The results were that one can reject the hypothesis of rugged topography does not influence the total cost of replacement of native forest. However , it does not reject the hypothesis that the distance from the area to be restored to the nearest urban center does not influence the total cost of replacement of the native forest and the distance from the area to be restored to the nursery that supplies seedling does not influence the total cost of replacement of native forests. After this first approach a serie of regressions, using the classical ordinary least squares (OLS) is performed. Were made a sensitivity analysis of the results obtained. The survey data was obtained by conducting a survey (questionnaire) to a series of entities of reforestation industry. All four hypotheses were tested. According to the tests , it can be said that the hypothesis of the impact of rugged topography on the total cost of replacement of native forest showed nonsignificant in all models. However, the first hypothesis of the impact of the degradation level on the value of the project was rejected in all models. The third hypothesis of the impact of the distance from the area to the nearest urban center on the value of the project was rejected in two models and fourth hypothesis of the impact of the distance from the area to be restored to the nursery that supplies seedling on the total cost of replacement native forest was rejected in one model. The replacement cost of a native forest of the Atlantic Forest biome was R$ 22 thousand a hectare. This study also outlines the developments of environmental economics over time, emphasizing its main characteristics. The conclusions highlight the main points of this work, a number of theoretical and managerial implications of this study is discussed and suggestions are made for further research in this area.